The Increase in Production Efficiency of Hydroponic Salad (A Case Study of Green Oakleaf Lettuce) - Athiwat Wangmai (2020)
© 2019 IOP Publishing Ltd. All rights reserved. The trend of growing hydroponic salad has been increasingly popular because consumers are more concerned about health nowadays. There are several kinds of salad. However, green Oakleaf lettuce was studied in this research because the smart farm in Mae On, Chiang Mai which was the farm in this case study grew green Oakleaf lettuce on 70 percent of its land. The problems found on the farm were: 1. there was no criteria of quality level of green Oakleaf lettuce production, 2. there was no efficient system of controlling factors which caused poor quality of green Oakleaf lettuce production. The solutions to the problems mentioned above were: 1. the criteria of quality level of green Oakleaf lettuce were set by taking green Oakleaf lettuce randomly from Nong Hoi Royal Project Foundation to measure its weight, diameter, height, the number of its leaves, and leaf area. All physical characteristics of green Oakleaf lettuce were analyzed to find the relations among them and the hypothesis was tested. The finding revealed that the weight was significantly associated with all other characteristics at the level of 0.05. Therefore, the weight was used to set up criteria and they were as follows: A grade level for lettuce weighed more than 200 grams, B grade level was between 150 and 200 grams, and C grade level weighed from 50 to 150 grams. After that, these criteria were utilized to divide the quality level of green Oakleaf lettuce on the smart farm in Mae On, Chiang Mai. The result was that 72.1 percent of green Oakleaf lettuce was A grade level, 27.9 percent was B grade level, and 4.65 percent was C grade level. 2. factors affecting the growth of lettuce were studied by using the quality control principles. The finding showed that the solution with greater than 25C had an effect on the growth of lettuce of 17.79 percent, water had an effect of 16.11 percent, nutrients had an effect of 13.56 percent, temperature higher than 25C in a greenhouse had an effect of 11.01%, diseases and bugs had an effect of 10.17%, air had an effect of 10.17 percent, seeds had an effect of 9.32%, light had an effect of 8.47%, and others had an effect of 3.39%.